Public opinion toward causes of road accident a case study at Graha Maju Malacca / Nur Aslina Mustapa and Edna Peter Guntili - Mustapa, Nur Aslina; Guntili, Edna Peter (Faculty of Administrative Science and Policy Studies, 2011)
Road accidents has becomes the big issues that always have been discuss by many parties in Malaysia. Almost every festive seasons, there will be lots of road accident occurred in major road in Malaysia. So, a case study has been run to measure the public opinion about the causes of road accidents. The causes of road accident will be dived into three which are the human factor, vehicle factor and also the traffic factor. Recommendation or alternatives that can be done in order to reduce the number of road accident in Malaysia.